A new feather mite, Aetacarus elanoides sp. n. (Acari: Gabuci-niidae), from the Swallow-tailed Kite Elanoides forficatus (Linnaeus) (Falconiformes: Accipitridae; Perninae) - Proctor, Heather; Zimmerman, Gina; Meyer, Kenneth (Zootaxa, 2006)
We describe a new species of the feather mite genus Aetacarus Gaud & Atyeo, 1975 from the norther n subspecies of the Swallow-tailed Kite, Elanoides forficatus forficatus (Linnaeus) (Falconiformes: Accipitridae) from the southeastern U.S.A. Aetacarus elanoides sp. n. differs from other described species in the genus by the following combination of features: male with terminal membranes as wide as or wider a t base than long and seta e h1 slightly spatulate a t tip; female with spatulate-mucronate seta e e2 and thick spine-like setae h1. This represents the first described feather mite from E. forficatus, and the first Aetacarus species described from a New World host.